Electrochemically exfoliated graphene oxide/iron oxide composite foams for lithium storage, produced by simultaneous graphene reduction and Fe(OH)3 condensation. (April 2015) - Xia, Zhen Yuan; Wei, Di; Anitowska, Elzbieta; Bellani, Vittorio; Ortolani, Luca; Morandi, Vittorio; Gazzano, Massimo; Zanelli, Alberto; Borini, Stefano; Palermo, Vincenzo
Abstract: We describe the production of graphene-based composites for energy storage, obtained by a combination of electrochemical and solution processing techniques. Electrochemically exfoliated graphene oxide sheets (EGO) are produced using an original setup that allows fast expansion of graphite flakes and efficient exfoliation of expanded graphite via an electrochemical route. The sheets are deposited on a sacrificial nickel foam together with an iron hydroxide colloidal precursor. Calcination treatment simultaneously renders the EGO foam conductive and transforms Fe(OH)3 into hematite ( α -Fe2 O3 ), yielding a nanoporous Fe2 O3 layer on the surface of the mesoporous EGO foam, creating an ideal structure for lithium storage. The obtained graphene/metal oxide hybrid is a continuous, electrically conductive three-dimensional (3D) composite featuring a hierarchical meso–nano porous structure. A systematic study of these composites, varying the Fe2 O3 :EGO ratio, is then performed to maximize their performance as nanostructured electrodes in standard coin cell batteries.